2007
DOI: 10.1099/jmm.0.46761-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection and prevalence of inducible clindamycin resistance in staphylococci

Abstract: Staphylococcus aureus and coagulase-negative staphylococci (CNS) are recognized as causing nosocomial and community-acquired infections in every region of the world. The resistance to antimicrobial agents among staphylococci is an increasing problem. Clindamycin (CL) is considered to be one of the alternative agents in these infections. This study demonstrates a simple, reliable method (double-disc diffusion test) for detecting inducible resistance to CL in erythromycin-resistance (ER-R) isolates of S. aureus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
106
7
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(135 citation statements)
references
References 18 publications
21
106
7
1
Order By: Relevance
“…The presence of more than one erm gene was not detected in S. aureus but it was observed in four SCN isolates. According to Martineau et al,in Canada,20.9% of the S. aureus were positive for the ermA gene and 66% of CNS were positive for the ermC gene, demonstrating that the prevalence of the ermA gene in S. aureus is slightly lower in comparison to other studies. 22 A multicenter study in 24 European university hospitals confi rmed the high prevalence of ermA gene and the low prevalence of ermC and ermB genes among 851 S. aureus.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The presence of more than one erm gene was not detected in S. aureus but it was observed in four SCN isolates. According to Martineau et al,in Canada,20.9% of the S. aureus were positive for the ermA gene and 66% of CNS were positive for the ermC gene, demonstrating that the prevalence of the ermA gene in S. aureus is slightly lower in comparison to other studies. 22 A multicenter study in 24 European university hospitals confi rmed the high prevalence of ermA gene and the low prevalence of ermC and ermB genes among 851 S. aureus.…”
Section: Discussionmentioning
confidence: 55%
“…14 In Turkey it was demonstrated that the prevalence of the cMLS B phenotype is higher than that of the iMLS B phenotype and the MS B phenotype is low, data similar to our study. 15,[18][19][20] A previous study conducted in our city evaluated 200 CNS and showed that only 2.5% of isolates presented the iMLS B resistance phenotype. 21 Therefore, one could speculate that the prevalence of the inducible phenotype is low in our city.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing frequency of staphylococcal infections among patients and changing patterns of antimicrobial resistance have led to renewed interest in the use of clindamycin therapy to treat such infections (13,14) . Clindamycin is frequently used to treat skin and bone infections because of its tolerability, cost, oral form and excellent tissue penetration, and the fact that it accumulates in abscesses and no renal dosing adjustments are needed (14) .…”
Section: Discussionmentioning
confidence: 99%
“…They studied 110 isolates of Staphylococcus aureus and determined that inducible resistance to clindamycin occurred in two-thirds of MRSAs, but was not seen with methicillin-sensitive S. aureus (MSSA). The ‘D-test’ (which is so called because of the shape of inhibition produced on the plate) was recommended for use in local microbiology laboratories to determine inducible resistance in staphylococci [2, 3]. Most routine laboratories may find it easier to rely simply on the results of erythromycin testing.…”
mentioning
confidence: 99%